Growth rate and projected age at sexual maturity for immature hawksbill turtles and green turtles foraging in the remote marine protected area of Aldabra Atoll, Seychelles - Sanchez, Cheryl L.; Bunbury, Nancy; Mortimer, Jeanne A.; A’Bear, Luke; Betts, Michael; von Brandis, Rainer; Burt, April J.; Cooke, Lorraine; van de Crommenacker, Janske; Currie, Jock C.; Doak, Naomi; Fleischer-Dogley, Frauke; et al. (Marine biology, 2023)
Changes in marine ecosystems from human stressors, and concerns over how species will respond to these changes have emphasized the importance of understanding and monitoring crucial demographic parameters for population models. Long-lived, migratory, marine vertebrates such as sea turtles are particularly vulnerable to changes. Life-history parameters like growth-in-body size can be largely influenced by environmental processes which can impact population growth. We analyzed a 40-year (1981–2021) capture-mark-recapture dataset from the protected UNESCO World Heritage Site, Aldabra Atoll, Seychelles, to estimate key population parameters, including body growth, for immature green turtles ( Chelonia mydas ) and hawksbill turtles ( Eretmochelys imbricata ). Curved carapace length (CCL) range was 34.3–110.9 cm (mean ± SD: 51.0 ± 11.4 cm, n = 1191) for green turtles and 28.7–89.4 cm (47.7 ± 14.4 cm, n = 538) for hawksbill turtles. Recapture events, with an 11-month minimum period, revealed a mean annual growth rate of 3.2 ± 1.5 cm year −1 for green turtles (n = 75) and 2.8 ± 1.4 cm year −1 for hawksbill turtles (n = 110). Hawksbill turtles exhibited a non-monotonic growth rate while no significant growth-size relationship was detected for green turtles. Green turtle mean annual growth per 10-cm size class was highest in the larger size classes (50‒69.9 cm). Hawksbill turtle growth rate was highest in the larger size classes (50‒69.9 cm) then declined in the largest size class (70‒79.9 cm). Green turtles and hawksbill turtles may spend > 8 and 18 years, respectively, using Aldabra, Seychelles, as a foraging ground.